Cuatro lecturas breves de La anunciación hecha a María de Paul Claudel - Longan Phillips, Shirley (Journal Of Modern Languages, 2014)
The Tidings Brought to Mary is the master piece of Paul Claudel (1868- 1946). This paper presents four short readings of this drama: a formal reading, a symbolic reading, a feminist reading, and a reading following the Lenin Garrido’s proposal in La imagen teatral.